Impact of sodium caseinate, soy lecithin and carrageenan on functionality of oil-in-water emulsions. (September 2019) - Koo, Charmaine K.W.; Chung, Cheryl; Fu, Jun-Tse Ray; Sher, Alexander; Rousset, Philippe; McClements, David Julian
Abstract: Oil-in-water emulsions are the main component of creamers, which are used to cream cold or hot coffee. These emulsions must provide the required lightening power and remain physically stable when introduced into hot acidic coffee solutions. In this study, model oil-in-water emulsions stabilized with mixed emulsifiers of sodium caseinate (0.5%) and soy lecithin (0.5%) were fabricated and their physical properties were examined over a range of pH values (pH 3.5 to 7). These model oil-in-water emulsions had strong lightening power ( L* ≈ 87) and good physical stability from pH 5.5 to 7 but were unstable to gravitational separation below pH 5 due to caseinate aggregation around its isoelectric point. Addition of λ-carrageenan (0.05 to 0.175%) to the formulations prior to homogenization effectively improved their pH stability, while addition of κ-carrageenan was ineffective. The significantly higher level of sulfated ester groups in λ-carrageenan may have created a strong electrostatic repulsion between the oil particles, inhibiting their association. Our study suggests that some of the caseinate in coffee creamers can be replaced with plant-based lecithins, but that a plant-based polysaccharide is also needed to ensure their stability when added to hot acidic coffees. Graphical abstract: Unlabelled Image Highlights: More consumers are buying plant-based milk for health and sustainability reasons. Model creamers were made with dairy and plant emulsifiers as a flexitarian approach. Model creamers had similar appearance and physical properties to commercial creamer. Model creamers made with milk caseinate aggregated at and below its isoelectric point. λ-Carrageenan improved physical stability of model creamers made with caseinate.